(untitled) (Research, Society and Development, 2023)
The objective of this article was to analyze the Study of Environmental Impacts (EIA) of the agrosilvopastoral project (agriculture and forestry integrated with livestock) at the Sitiozinho farm, located in the municipality of Nazaré do Piauí/PI. To achieve the proposal, use a qualitative and descriptive approach in the analysis and evaluation, based on bibliographic research and environmental legislation. It was possible to verify that the study in question met the minimum requirements maintained by the environmental legislation at the time of the preparation of the document. However, for future analyzes of studies related to the theme, it is suggested to update the controls that will be used in the evaluation of environmental performance and control measures in order to fully comply with the constant updates of current environmental legislation.